Antibodies to MOG and AQP4 in children with neuromyelitis optica and limited forms of the disease. Issue 8 (8th December 2015) - Lechner, Christian; Baumann, Matthias; Hennes, Eva-Maria; Schanda, Kathrin; Marquard, Klaus; Karenfort, Michael; Leiz, Steffen; Pohl, Daniela; Venkateswaran, Sunita; Pritsch, Martin; Koch, Johannes; Schimmel, Mareike; et al.
Abstract : Objective: To determine the frequency and clinical-radiological associations of antibodies to myelin oligodendrocyte glycoprotein (MOG) and aquaporin-4 (AQP4) in children presenting with neuromyelitis optica (NMO) and limited forms. Methods: Children with a first event of NMO, recurrent (RON), bilateral ON (BON), longitudinally extensive transverse myelitis (LETM) or brainstem syndrome (BS) with a clinical follow-up of more than 12 months were enrolled. Serum samples were tested for MOG- and AQP4-antibodies using live cell-based assays. Results: 45 children with NMO (n=12), LETM (n=14), BON (n=6), RON (n=12) and BS (n=1) were included. 25/45 (56%) children had MOG-antibodies at initial presentation (7 NMO, 4 BON, 8 ON, 6 LETM). 5/45 (11%) children showed AQP4-antibodies (3 NMO, 1 LETM, 1 BS) and 15/45 (33%) were seronegative for both antibodies (2 NMO, 2 BON, 4 RON, 7 LETM). No differences were found in the age at presentation, sex ratio, frequency of oligoclonal bands or median EDSS at last follow-up between the three groups. Children with MOG-antibodies more frequently (1) had a monophasic course (p=0.018) after one year, (2) presented with simultaneous ON and LETM (p=0.004) and (3) were less likely to receive immunosuppressive therapies (p=0.0002). MRI in MOG-antibody positive patients (4) less frequently demonstrated periependymal lesions (p=0.001), (5) more often were unspecific (p=0.004) and (6) resolved more frequently (p=0.016). Conclusions: 67% of all children presenting with NMO or limited forms tested positive for MOG- or AQP4-antibodies. MOG-antibody positivity was associated with distinct features. We therefore recommend to measure both antibodies in children with demyelinating syndromes.